Three new species of Tricholoma from Costa Rica - Ovrebo, Clark L.; Hughes, Karen W.; Halling, Roy E. (Phytotaxa, 2019)
Three new species of Tricholoma are described from Costa Rican montane forests with additional collections cited from the United States. The new species are Tricholoma felschii sp. nov., Tricholoma costaricense sp. nov. and Tricholoma atratum sp. nov. A discussion of Tricholoma luteomaculosum is also included. These taxa share morphological features of strong farinaceous odor and taste, pseudoparenchymatous pileal subcutis, and rugulose pileus at some stage of development. In addition, cheilocystidia occur in two of the taxa but not the third. Phylogenies are presented based on ITS sequences.